2014
DOI: 10.1097/qai.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Entry Inhibitors Alters HIV Infectiousness and Sensitivity to Broadly Neutralizing Monoclonal Antibodies

Abstract: Background: The development of envelope-specific neutralizing antibodies that can interfere with viral entry into target cells is important for the development of an HIV-1 vaccine. Another means of blocking viral entry is through the use of entry inhibitors such as the CCR5 inhibitor maraviroc (MVC), which can also repel cell-free virus particles from the cell surface. For this reason, we hypothesized that exposure to entry inhibitors might alter viral infectiousness and sensitivity to antibody-mediated neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Reactivity to other epitopes, such as CD4bs and MPER of gp41, may be caused by indirect changes in the Env trimer structure, which is accompanied by mutations in the CCR5-binding region, because the effect on neutralization by NAbs to CD4bs and MPER of gp41 was not uniform among studies by others and us. Although KK 652-67 was highly sensitive to anti-CD4bs NAbs, its sensitivity decreased in previous studies using variants resistant to VCV and MVC (18,38,39,56). Neutralization by NAb 10E8, targeting the MPER region of gp41, did not differ between KK WT and KK 652-67 , but the sensitivity to NAbs against MPER was affected in previous studies using variants resistant to other CCR5 antagonists (39,56).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Reactivity to other epitopes, such as CD4bs and MPER of gp41, may be caused by indirect changes in the Env trimer structure, which is accompanied by mutations in the CCR5-binding region, because the effect on neutralization by NAbs to CD4bs and MPER of gp41 was not uniform among studies by others and us. Although KK 652-67 was highly sensitive to anti-CD4bs NAbs, its sensitivity decreased in previous studies using variants resistant to VCV and MVC (18,38,39,56). Neutralization by NAb 10E8, targeting the MPER region of gp41, did not differ between KK WT and KK 652-67 , but the sensitivity to NAbs against MPER was affected in previous studies using variants resistant to other CCR5 antagonists (39,56).…”
Section: Discussionmentioning
confidence: 92%
“…Although KK 652-67 was highly sensitive to anti-CD4bs NAbs, its sensitivity decreased in previous studies using variants resistant to VCV and MVC (18,38,39,56). Neutralization by NAb 10E8, targeting the MPER region of gp41, did not differ between KK WT and KK 652-67 , but the sensitivity to NAbs against MPER was affected in previous studies using variants resistant to other CCR5 antagonists (39,56). Further studies using multiple variants resistant to various CCR5 antagonists are required to clarify the relationship between resistance to CCR5 antagonists and exposure of epitopes and to test our hypothesis that CCR5 antagonist escape mutations affect the Env structure, thereby altering its ability to interact with CCR5 and also the sensitivity to NAbs targeting the CCR5-binding region.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the β-galactosidase may be measured using different assays reflecting the number of cells that turn blue after X-gal staining and the activity of luciferase is quantified by the luminescence intensity that is proportional to the number of infectious viruses present in the examined specimen. Altogether, the cell line is a sensitive and easy diagnostic tool that is widely used to estimate HIV, SIV, and SHIV infectious titer and to evaluate the neutralization (NT) potency of tested sera [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. It has been shown that TZM-bl cells are infected with ecotropic gamma-retrovirus [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…After 2010, availability of, and accessibility to, antiretroviral drugs during pregnancy and lactation have increased. The programs of prevention of mother-to-child transmission (PMTCT) of HIV yielded 2 antiretroviral (ARV) prophylaxis options, including regimen A (prophylactic ARV drugs are given to the mothers and children during the risk period); and regimen B (antiretroviral therapy is given to the mothers during the risk period), or regimen B+ (extending regimen B to lifelong treatment) [20]. In the WHO’s 2010 recommendations, women living with HIV who opted to breastfeed were recommended to practice exclusive breastfeeding (EBF) until the infant was 6 months old, introduce appropriate complementary foods thereafter, and continue breastfeeding for the first 12 months of the infant’s life.…”
Section: Introductionmentioning
confidence: 99%